Salary Satisfaction and Employee Performance: Work Motivation’s Mediating Role in CV Eazywear Indonesia - Pratiwi, Shinta; Rifani , Ahmad (Jurnal Maksipreneur, 2025)
CV Eazywear Indonesia faces ongoing gaps between production targets and output, suggesting dissatisfaction with payroll practices that reduce work motivation and performance. This study investigates whether salary satisfaction impacts employee performance directly and indirectly through work motivation. A quantitative survey using a closed-ended questionnaire was given to all 40 permanent employees identified by census from production and support departments. Measures assessed pay satisfaction, work motivation, and job performance. Data were analyzed with Partial Least Squares Structural Equation Modeling in SmartPLS 4.0, including tests for convergent and discriminant validity and reliability. Results show that salary satisfaction positively affects work motivation (β = 0.805) and performance (β = 0.455). Work motivation boosts performance (β = 0.496) and mediates the relationship between salary and performance (indirect β = 0.399). R² values for performance and motivation are 0.817 and 0.648, indicating strong explanatory power. The findings highlight the value of fair, transparent, and well-communicated payroll management in boosting motivation and productivity in labor-intensive garment operations. This study is limited to one firm with a small sample, constraining generalizability. Future research should use multi-site, longitudinal designs and include objective performance metrics and controls.